GLOBAL STABILITY AND PERSISTENCE OF THREE SPECIESFOOD WEB INVOLVING OMNIVORY - Naji, Raid (Iraqi Journal of Science, 2024)
In this paper, the dynamics of a three species food web model consisting ofproducers, primary consumers and omnivory is studied analytically as well asnumeri-cally. The existence of equilibrium points and local stability analysisfor this model is carried out together with a bifurcation analysis. Theoccurrence of hopf bifurcation is also investigated. The persistence conditionsof the food web model are established by using average Lyapunov function.The global stability analysis of the food web model is also presented with helpof Lyapunov method. Finally, in order to confirm our analytical results,numerical simulation is carried out for suitable choices of parameters values. Itis observed that, the existence of omnivory in a food web plays a vital role inthe stability of the dynamical behavior of the system.